Household electricity consumption in the Philippines - Dalusung, Alberto R. III
Past efforts on energy conservation programs have been directed largely at industrial and commercial establishments, which have traditionally been large energy users. The growing residential power demand, estimated at 6,336 GWh and accounting for 29.7 percent of 1992 power consumption, also opens prospects for energy conservation. The study assesses the characteristics of household electricity demand in Metro Manila and identifies areas where demand management schemes can have the greatest impact on the power supply base. The study benefited largely from the 1989 household energy consumption survey conducted by the then Office of Energy Affairs under the World Bank Energy Sector Management Assistance Program. Review of the size and structure of household electricity demand indicates large potential energy savings from the use of more efficient lighting, airconditioning and refrigeration. The cost of conserved energy from the use of more efficient lighting, airconditioning and refrigeration. The cost of conserved energy from the use of efficient energy using devices is far less than the cost of installing additional power capacity. An intensified and sustained nationwide energy conservation program can significantly required capital investments for power development. Energy conservation also addresses the growing environmental issue while lowering energy imports and thus improving the country's balance of payments position. The study emphasizes that the gains achieved from earlier efforts can only be sustained and advanced with the synchronization of various efforts from both the legislative and executive branches of government. The support of the private sector, covering the power utilities, media, non-government organizations and consumers, is also imperative. Among various recommendations, the restructuring of power tariffs is deemed to be the single most effective factor in promoting energy conservation. By providing the right pricing signals, consumers will be compelled to orient their purchasing decisions towards energy efficient appliances and technologies and to alter their power consumption behavior.
Keywords: Energy consumption; Power utilities